HOW CLASSIFY MISTAKES AND SHORTCOMINGS IN REVIEWS OF SPECIAL AND SCIENTIFIC WORKS - STOFFA, Jan; STOFFOVA, Veronika (Trends in education, 2012)
The study presents an original and universal proposal of classification of mistakes and shortcomings in reviews of special and scientific works. The classification follows from the generally accepted requirement that the reviewer of a special or scientific work has to appreciate all significant positive values of the work as well as to point out all significant mistakes and shortcomings of it. The informational value and scientific truth of presented information and also respecting of copyright and scientific ethics were accepted as base criterions of classification. Each reviewer has to point out all key and other essential mistakes and shortcomings in fulfilling the criteria. Mistakes and shortcomings should be ordered not sequentially but characterized in category groups with presenting some representatives from each group as examples. Didactical mistakes and shortcomings and that ones which are not connected with distortion of information he/she should point out only from educational viewpoint.
Keywords: reviews of special and scientific works; shortcomings of special and scientific works.